Digital production management of the pagelaran Ketoprak Mataram program in RRI Yogyakarta during Covid-19 pandemic - Afifah, Putri Afifah; Fajar Junaedi, Fajar Junaedi (COMMICAST, 2022)
This research was motivated by the important role of digital content production management at the Ketoprak Mataram RRI Programa 4 Yogyakarta event and how to implement health protocols during the pandemic. This paper aims to find out how to manage digital content production for the Mataram Ketoprak Show program and the application of health protocols during the production of the RRI Program 4 Yogyakarta Ketoprak Mataram Show program during the pandemic. The method used is a case study method while data collection techniques are carried out by in-depth interviews, observation, documentation, and archival recordings. The results showed that during the production process due to the pandemic, RRI Programa 4 Yogyakarta employees had succeeded in designing new strategies and concepts to continue to hold the Mataram Ketoprak Performance. They use the media in the form of Live Streaming via the YouTube platform @RRIJOGJAOFFICIAL. The production management model that is applied to the intended digital content can go through several stages, namely pre-production, production, and post-production. In addition, good health protocols have also been implemented properly to minimize the spread of COVID-19 virus transmission at all stages carried out during the production process. at the Ketoprak Mataram Program RRI Program 4 Yogyakarta has been implemented and implemented well, as well as the implementation of health protocols according to the standards that have been set during the pandemic.